2005
DOI: 10.1021/jp053311a
|View full text |Cite
|
Sign up to set email alerts
|

New Insight into the Solid Electrolyte Interphase with Use of a Focused Ion Beam

Abstract: The formation and evolution of the solid electrolyte interphase (SEI) film on the surface of natural graphite spheres in the electrolyte of 1 M LiPF 6 in ethylene carbonate (EC) and dimethyl carbonate (DMC) (volume ratio 1:1) were investigated with use of focused ion beam (FIB) technology. Secondary electron FIB images clearly show the surface and cross-section morphology of the SEI film. The composition variation along the surface and cross section of the SEI film was also explored by the elemental line scan … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
66
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(67 citation statements)
references
References 37 publications
1
66
0
Order By: Relevance
“…It is well known that the loss of continuity and conductivity within battery electrodes caused by micro-scale fracture is one of the major causes for the degradation in Li-ion batteries [1][2][3]. Specific effects include the loss of electrical contact, isolation of active materials from the conductive matrix, and increased cell internal resistance [4].…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that the loss of continuity and conductivity within battery electrodes caused by micro-scale fracture is one of the major causes for the degradation in Li-ion batteries [1][2][3]. Specific effects include the loss of electrical contact, isolation of active materials from the conductive matrix, and increased cell internal resistance [4].…”
Section: Introductionmentioning
confidence: 99%
“…Investigations revealed that during cycling tests, electrolytes penetrated spherical graphite, causing surface cracks (Zhang et al, 2005). The capacity of spherical graphite, however, faded while process.…”
Section: Resultsmentioning
confidence: 99%
“…This damage feature is consistent with those reported in the literature for carbon electrodes. [11,12,[51][52][53] It is likely that most damage to the uncoated CFs occurred prior to the establishment of the solid electrolyte layer. [7,8] …”
Section: Microstructural and Compositional Characterization Of Sn-mentioning
confidence: 99%